Rupture uterus: a retrospective analytical study - Prajapati, Shetal S.; Goswami, Kamal D.; Dudharejia, Kavita M.; Kannar, Avani N.; Parmar, Prakash H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Over 500,000 women die each year due to complications of pregnancy and childbirth, a number that has remained relatively unchanged since 1990, when the first global estimates of the burden of maternal mortality were developed (WHO 2005). Objective of present study was to find out risk factors, management, related complications and associated maternal morbidity and mortality with rupture uterus. Methods: A retrospective analytical study was performed at Department of Obstetrics and Gynecology, PDU Medical College, Rajkot, Gujarat, India over a period of 3 years during 2014-2016. Evaluation of maternal age, parity, SE status, booking status, obstetric risk factors, duration of hospital stay, causes of rupture uterus, Management, intra-op and post-operative complications, maternal morbidity and mortality was done. Results: Total 29 cases of rupture uterus were found during study period. Most of them belong to age group of 21-30 (77.17%), Primipara (41.3%), Lower socioeconomic status (86.2%) and unbooked (65.52%) cases. Most common cause of rupture uterus was prolonged obstructed labor (51.72%) while scarred uterus (41.73%), transverse lie (3.44%) and injudicious use of oxytocin (3.44%) were others. In 16 cases obstetric Hysterectomy (55.17%) was performed while in 13 cases repair (44.82%) was done. We have found 2 cases of maternal death (6.89%) while study period with rupture uterus. Conclusions: Present retrospective analytical study has concluded that rupture uterus is a life threatening complication. Proper antenatal and intrapartum care, identification of high risk factors, promotion of skilled attendance at birth and institutional delivery are key factors in reduction and early diagnosis.